Pattern of Organism and Drug Sensitivity on Culture and Sensitivity of Pus from Soft Tissue Abscesses in Pediatric Patients - Saqib Ismail, Tahseen Ismail, Syed Zakir Hussain Shah, Aqdas Saqib, Muhammad Uzair, Masroor Hussain Sharfi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Soft tissue abscesses is one of the most commonly observed complication in children. This infection may impart the longer stay at hospital and also increase the cost of medical care. Objective: The study was carried out to find the pattern of organisms and the sensitivity of drugs from the pus produced in soft tissue abscesses among patients. Study design: It is cross-sectional study conducted from January 2020 to November 2022. Material and Methods: The study was conducted at the pediatric department of the Div. HQ teaching hospital Mirpur, Azad Jammu and Kashmir. The study was carried out on 160 patients having at least one abscess on their body. The study also collected information about the predisposing factor that could have led to abscess formation. The site of distribution of the abscess was also analyzed. The abundance of microorganisms that were isolated from the samples of abscesses was also studied. Results: it was found that in most of the patients (45.5%) the blunt trauma was the main cause of formation of abscess. The common cause of abscess at extremities was blunt trauma. The common cause of abscess at head and neck site was upper respiratory tract infection and lymphadenitis. The head and neck area along with lower limb was the site that had most of the abscess. Conclusion: In our study the blunt trauma at extremities was found to be main factor leading to pus formation from smooth tissue abscess among infants. The most common region where pus was formed was extremities, head and neck area and lower limb area. Keywords: klebsiella pneumonia and Soft tissue abscesses.